Evaluation of Analgesic, Antidiarrheal and CNS Depressant Activity of Seed Extracts of Trigonella foenum graecum L. - Naima, Jannatul; Proma, Nawreen Monir; Islam, Mohammed Rashedul; Hossain, Md Rajib; Rashma, Salma Sultana; Hossain, Mohammed Kamrul (Chittagong University Journal of Biological Sciences, 2024)
The methanolic extract of Trigonella foenum graecum L. showed significant peripheral analgesic activity at a dose of 400 mg/kg and 200 mg/kg body weight with percentage of inhibition of acetic acid induced writhing 68.10%(P<0.001) and 52.80%(P<0.001), respectively compared to the standard diclofenac (62.50%)(P<0.001) group.The crude methanolic extract also showed significant antidiarrheal activity by castor oil induced diarrhea test with percentage of inhibition of defecation 45.16%(400mg/kg dose,p<0.001) and 38.71%(200mg/mg dose,p<0.001) compared to the standard loperamide (61.29%).In case of CNS depressant activity by phenobarbitone induced sleeping time test,the crude methanolic extract significantly reduced sleep latency by 84.16% and increased the duration of sleep by 39.03% and 36.47% compared to the standard diazepam (89% and 44.58%, respectively). In light of available literature,these findings provided some scientific justification for significant folkloric use of the seeds of the plant for the treatment of algesia, CNS depression and diarrhea. The Chittagong Univ. J. B. Sci. 9(1&2):57-62,2019